2018
DOI: 10.1111/cbdd.13334
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine‐based pyrazoles as cyclin‐dependent kinase 2 inhibitors: Design, synthesis, and biological evaluation

Abstract: A series of new pyrimidine-pyrazole hybrid molecules were designed as inhibitors of cyclin-dependent kinase 2. Designed compounds were docked using Glide and the compounds showing good score values and encouraging interactions with the residues were selected for synthesis. They were then evaluated using CDK2-CyclinA2 enzyme inhibition by a luminescent ADP detection assay. We show that of the 26 compounds synthesized and evaluated, at least 5 compounds were found to be highly potent (IC < 20 nm); which can be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cyclin-dependent kinases (CDKs) are one class of serine/threonine proteins. These serine/threonine proteins are renowned for their important functions in the regulation of cell divisions [23]. Cancer and other disorders associated with aberrant cellular production can be effectively treated by blocking several enzymes that regulate the cell cycle's progression [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinases (CDKs) are one class of serine/threonine proteins. These serine/threonine proteins are renowned for their important functions in the regulation of cell divisions [23]. Cancer and other disorders associated with aberrant cellular production can be effectively treated by blocking several enzymes that regulate the cell cycle's progression [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to develop new anti-cancer agents [ 2 , 3 ]. Literature survey indicated that pyrimidine analogs are of considerable interest in drug discovery [ 4 , 5 , 6 , 7 , 8 ]. They possess remarkable biological activity especially as anti-cancer and anti-viral agents due to their resemblance to cellular pyrimidine bases involved in nucleic acids formation.…”
Section: Introductionmentioning
confidence: 99%